(untitled) (Regional aspects of productive forces development of Ukraine, 2023)
Introduction. The article is devoted to the study of the process of forming the operational strategy of national enterprises at the current stage, as the main means that allows effective use of the resources and production capabilities of the enterprise and ensures the achievement of the desired result of activity, as well as helps to stabilize the national economy in today’s realities. Goal. Research on the technology of selecting tools for the formation of an effective operational strategy of the national enterprise. To achieve this goal, the following tasks were formulated: to investigate the essence of the operational strategy and its place in the general strategy of the national enterprise; to describe the main stages of forming the operational strategy of the enterprise; to formulate an effective methodological toolkit for the formation of an effective operational strategy of the national enterprise in the conditions of modern economic and political challenges. Research methods. Methods of comparative, systematic, structural analysis, and generalization are used. Results. The essence of the concept of the enterprise operational strategy was studied, the place of the operational strategy in the general strategy of the enterprise was determined. Thus, the strategy of the organization is in essence a general plan and a set of measures for its development in general, while the operational strategy is a certain important component of the overall strategy. In this regard, it is important to note that the operational strategy determines how to manage the key organizational links of the operational system, as well as how to ensure the implementation of strategically important operational tasks. The main stages of the formation of the company’s operational strategy are characterized and the key aspects and tools that are important for the effectiveness of this strategy in today’s conditions are highlighted. Accordingly, the following aspects are key ones to build an effective operational strategy of the enterprise: the combination of opportunities identified during the analysis of the strategy and its own strengths, the creation of a positive synergistic relationship between them, as well as a clear calculation of the enterprise’s break-even point. It has been studied that at the moment, the basic principle of profit maximization for national enterprises recedes to a secondary position in comparison with the importance of functioning stably even at the break-even point and thereby supporting the national economy. It is proposed to organize support for such entrepreneurs at the level of state and local funding and by providing them with certain incentives. An important principle in the construction of the operational strategy of such enterprises should be clear and complete control of the break-even point. Conclusions. The main provisions of the scientific article will contribute to the formation of an effective operational strategy of national enterprises.